Gliricidia sepium: genetic resources for farmers - Stewart, J; Allison, G; Simons, A (Oxford Forestry Institute, University of Oxford, 1996)
Gliricidia sepium (Jacq.) Steud. is a typical example of a multipurpose tree species, providing essential products and services on farms in the tropics, yet with no industrial role and therefore largely ignored by researchers and foresters until quite recently. In the mid-1970s a shift in donor emphasis in forestry towards small-scale and community initiatives led to a sudden increase in research interest (and donor investment) in trees and shrubs which farmers had already, in many cases, been using for centuries. Professionals in the fields of forestry, agriculture and rural development had hitherto paid little attention to these species. The result has been a huge accumulation, since the early 1980s, of research findings on all aspects of the biology, use and management of G. sepium...